2016
DOI: 10.21859/jne-05043
|View full text |Cite
|
Sign up to set email alerts
|

Nursing Students' Disposition toward Critical Thinking and its Relationship with their Academic Performance

Abstract: Introduction: In order to improve nurses' critical performance and the quality of nursing care, nursing education must not only provide nursing students with specialized knowledge, but also develop their critical thinking skills. For nurses and nursing students to be efficient, they must be capable of critical thinking. The present study aimed to examine nursing students' disposition toward critical thinking and its relationship with their academic performance. Methods: This was a descriptive correlational stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 1 publication
2
7
0
Order By: Relevance
“…According to the results of the current study, no significant difference was observed between male and female students in terms of the score of critical thinking disposition. Results of studies by Mousazadeh et al (31), and Haghshenas and Sajjadian (25), also confirmed the current study findings. These studies conducted on critical thinking disposition, also reported no significant difference between male and female students in this regard (5,31).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…According to the results of the current study, no significant difference was observed between male and female students in terms of the score of critical thinking disposition. Results of studies by Mousazadeh et al (31), and Haghshenas and Sajjadian (25), also confirmed the current study findings. These studies conducted on critical thinking disposition, also reported no significant difference between male and female students in this regard (5,31).…”
Section: Discussionsupporting
confidence: 92%
“…Results of studies by Mousazadeh et al (31), and Haghshenas and Sajjadian (25), also confirmed the current study findings. These studies conducted on critical thinking disposition, also reported no significant difference between male and female students in this regard (5,31). In addition, no significant association was observed between the total score of critical thinking disposition and students' age; the results were consistent with those of Gharib et al (28), although more disposition and use of critical thinking skills were expected by age and experience increase (28).…”
Section: Discussionsupporting
confidence: 92%
“…e American Nurses Association (1998), the National Nurses United (1992), and the Accreditation Commission of the National Nurses United (2002) also proposed learning it as an integral component of nursing education and required nursing instructors to teach it to nursing students [2]. In fact, nursing students should be trained to develop their critical spirit and research capabilities and equip themselves with critical thinking as a valuable tool in a way that their decision-making ability and performance are improved in complicated clinical circumstances after their graduation [10] In this regard, many universities around the world are looking for new and appropriate educational methods that can organize people and their educational system and lead to the expansion and improvement of clinical decision-making, problem solving, and continuous and self-centered learning in medical students. In order to address this concern, supporting critical thinking skills and investing in training and continuous assessment of changes in cognitive processes along with psychomotor and attitudinal domains in caring practices has become particularly important.…”
Section: Introductionmentioning
confidence: 99%
“…Nursing instructors are therefore required to broaden their knowledge about critical thinking disposition [12]. Although the research suggests a high score of critical thinking in undergraduate nursing students [10,13], low levels of critical thinking skills have been reported in literature [6,11,14]. e effects of individual factors on critical thinking skills have been also reported differently in literature.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation